Analysis of the Thermal Residual Stress and Parametric Simulation in Laser Cladding Using COMSOL Multiphysics - Diwakar V.; Sharma A.; Yusufzai M.Z.K.; Vashista M. (My University, 2025)
Laser cladding is a method of additive manufacturing in which metallic powders or wire are melted and fused onto a substrate using a high-energy laser and create a layer of material with desired thickness and composition which improve the surface properties of the substrate. The estimation of the thermal behavior in the laser cladding is more difficult due to the complex melt pool dynamics which having rapid cooling and solidification of the deposited material on the substrate. However, in laser cladding, involvement of various process parameters and development of the thermal residual stresses during the process affect the mechanical properties of the cladded material. Therefore, it is very important to analyze the process parameters and thermal residual stress to improve the quality of the deposited material. In the simulation, preplaced powder feeding system is used to analyze the effect of the process parameters on the thermal residual stresses. The laser power and scanning speed are critical process parameters which directly affect the amount of heat input into the substrate material. During the parametric simulation, a direct relation was showed between the laser power and temperature distribution but inversely relation is appeared with increasing scanning speed. As the laser power increases, the temperature gradient between the melted material and the substrate material also increases, which corresponds to the development of higher thermal residual stresses in the substrate. However, in case of higher scanning speed, there is less thermal residual stress due to having less time to melt and solidify for deposited material which create less temperature gradient but for the lower scanning speed higher thermal residual stress appeared due to higher heat flux and temperature gradient. © ASM International 2024.